Lichen planus following the lines of Blaschko. - Miteva, L.; Semkova, K. (European Journal of Pediatric Dermatology, 2011)
Lichen planus (LP) is an inflammatory skin disease. Although relatively common in adults, LP is very rare in children. Its most common clinical presentation is with bilateral, symmetrical, small, pruritic, violaceus papules. Linear distribution could be observed occasionally and in children the linear forms always follow the lines of Blaschko. These lines, which can be observed in case of cutaneous mosaicism, follow pathways of cell migration during ectodermal development. We report a case of linear LP in the lines of Blaschko in a 16-year-old adolescent seen and followed-up at our clinic.